PERFORMANCE EVALUATION OF EMERGING JPEGXR COMPRESSION STANDARD FOR MEDICAL IMAGES - Basit, M. A.; Raja, G. (The Nucleus, 2012)
Medical images require lossless compression as a small error due to lossy compression may be considered as a diagnostic error. JPEG XR is the latest image compression standard designed for variety of applications and has a support for lossy and lossless modes. This paper provides in-depth performance evaluation of latest JPEGXR with existing image coding standards for medical images using lossless compression. Various medical images are used for evaluation and ten images of each organ are tested. Performance of JPEGXR is compared with JPEG2000 and JPEGLS using mean square error, peak signal to noise ratio, mean absolute error and structural similarity index. JPEGXR shows improvement of 20.73 dB and 5.98 dB over JPEGLS and JPEG2000 respectively for various test images used in experimentation.